Impact of Fatigue Characteristics on Quality of Life in Patients After Heart Transplantation. Issue 6 (November 2017) - Chou, Yu-Ying; Lai, Yeur-Hur; Wang, Shoei-Shen; Shun, Shiow-Ching
Abstract : Background: Fatigue has been identified as a major symptom in heart transplant (HTx) patients; however, researchers have not examined the role of fatigue characteristics (ie, intensity, interference, and duration) in the quality of life (QOL) of HTx patients. Objective: The aim of this study was to explore differences in physical and mental aspects of QOL by patient characteristics, as well as the association between fatigue characteristics and QOL in HTx patients after considering other confounding factors (symptom distress and psychological distress). Methods: A cross-sectional study was conducted in which patients completed the Transplant Symptom Frequency and Symptom Distress Scale, the Fatigue Symptom Inventory, the Hospital Anxiety and Depression Scale, and the 12-item Short-Form Health Survey. Multiple regressions were used to identify factors significantly related to QOL. Results: A total of 126 patients reported moderate levels of fatigue intensity, mild fatigue interference, and low QOL scores in the physical and mental domains. Patients with better physical and cardiac function and lower symptom distress and fatigue interference had better scores on the physical aspect of QOL (explaining 30.7% of the variance); patients with lower fatigue interference, anxiety, and depression had better scores on the mental aspect of QOL (explaining 50% of the variance). Conclusions: Fatigue interference had a greater influence on QOL domains than fatigue intensity. The degree to which fatigue interferes with daily life should be assessed, and suitable interventions should be introduced in clinical settings to help patients manage their fatigue and improve their QOL.